In Vitro Antioxidant Activity, Flavonoid and Phenolic Contents of 70% Methanol Extract from Purple and Yellow Passion Fruit Peel - Khoirul Ngibad; Siti Nur Husnul Yusmiati; Setyo Dwi Santoso; Firda Inayah; Rizky Dwi Nur Faizi (Indonesian Journal of Chemistry and Environment, 2023)
Peel of purple and yellow passion fruit has the potential to be an antioxidant. The flavonoid and total phenol compound groups are two examples of natural antioxidant compounds that can potentially be antioxidants. Many studies have used 70% methanol solvent to extract flavonoids and total phenolics from plants. The aim of this study is to analyze the potential of 70% methanol extract from the peel of purple and yellow passion fruit as an in vitro antioxidant using the DPPH method, total flavonoid, and phenolic levels. The passion fruit peel powder was macerated with 70% methanol for four days. The total flavonoid contents were determined using quercetin, and total phenols were determined using gallic acid. The 2.2-diphenyl-1-picrylhydrazyl (DPPH) was used for in vitro antioxidant activity by determining the percent inhibition of DPPH radicals. The flavonoid content in the 70% methanol extract of purple and yellow passion fruit peel is 1.2824 and 1.9775 mg QE/g extract, respectively. In contrast, the total phenolic content in 70% methanol extract of purple and yellow passion fruit peel is 15.8 and 3.6 mg GAE/g extract, respectively. The 70% methanol extract of purple passion fruit peel at a concentration of 80 mg/L resulted in a more significant percent inhibition of DPPH free radicals (72.80 %) than yellow passion fruit (64.91 %). In conclusion, the results suggest that 70 % methanol extract from purple and yellow passion fruit peel can decrease free radicals and be a natural antioxidant.Keyword: Antioxidant activity, Flavonoid, Methanol extract, Passion fruit peel, Total phenol